2018
DOI: 10.1111/joa.12890
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal malformations of Meox1‐deficient zebrafish resemble human Klippel–Feil syndrome

Abstract: Klippel–Feil syndrome is a congenital vertebral anomaly, which is characterised by the fusion of at least two cervical vertebrae and a clinically broad set of symptoms, including congenital scoliosis and elevated scapula (Sprengel's deformity). Klippel–Feil syndrome is associated with mutations in MEOX1. The zebrafish mutant choker (cho) carries a mutation in its orthologue, meox1. Although zebrafish is being increasingly employed as fidelitous models of human spinal disease, the vertebral column of Meox1‐defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…Previous studies suggested that mutations in GDF6 [10,36] and GDF3 [13] were associated with autosomal dominant KFS. In addition, a truncating mutation in MEOX1 [11,12,37] and a homozygous nonsense mutation in MYO18B [14,38] were identified in autosomal recessive KFS families. Using WES, a homozygous frameshift mutation (c.299delT: p. L100fs) in RIPPLY2 was confirmed as a novel gene for autosomal recessive KFS in a consanguineous family [15,39].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that mutations in GDF6 [10,36] and GDF3 [13] were associated with autosomal dominant KFS. In addition, a truncating mutation in MEOX1 [11,12,37] and a homozygous nonsense mutation in MYO18B [14,38] were identified in autosomal recessive KFS families. Using WES, a homozygous frameshift mutation (c.299delT: p. L100fs) in RIPPLY2 was confirmed as a novel gene for autosomal recessive KFS in a consanguineous family [15,39].…”
Section: Discussionmentioning
confidence: 99%
“…Mutant choker of zebrafish meox1 gene ( Dauer et al, 2018 ) has also been proposed as a Klippel–Feil syndrome model in group 35 ( Supplementary Table 1 ), a disease caused by mutations in human ortholog MEOX1 gene (see Mortier et al, 2019 ). The vertebral fusion, congenital scoliosis, and pectoral girdle asymmetry observed in this mutant almost exactly resembles the cervical vertebra fusions, congenital scoliosis, and skeletal alterations found in patients with this disease ( Dauer et al, 2018 ).…”
Section: Zebrafish Models For Human Skeletal Diseasesmentioning
confidence: 99%
“…Recent studies have suggested that failed development of the craniocervical junction that underlies AO could be caused by defective somitogenesis in the cervical region resulting from gene mutations [5][6][7]. According to OMIM (Online Mendelian Inheritance in Man), Genecards, and MGI (mouse genome informatics)( MP:0010728), it has been reported that mutations in MEOX1(GCID:GC17M043640, MIM:600147), MYO18B(GCID:GC22P025742, MIM:607295), and the HOX family of genes are associated with AO [7][8][9]. A study by David (1999) of 30 cases of Klippel-Feil syndrome (KFS) found that a mutation in the Hox gene was the mechanism possibly responsible for atlas assimilation, while reduced or impaired Pax-1 gene expression may result in vertebral fusions [10].…”
Section: Introductionmentioning
confidence: 99%
“…The principal etiology of AO is the impaired development of the bone of the cranio-cervical junction, leading to improper segmentation of the vertebrae. Recent studies have suggested that failed development of the craniocervical junction that underlies AO could be caused by defective somitogenesis in the cervical region resulting from gene mutations [5][6][7]. According to OMIM (Online Mendelian Inheritance in Man), Genecards, and MGI (mouse genome informatics)( MP:0010728), it has been reported that mutations in MEOX1(GCID:GC17M043640, MIM:600147), MYO18B(GCID:GC22P025742, MIM:607295), and the HOX family of genes are associated with AO [7][8][9].…”
Section: Introductionmentioning
confidence: 99%